An Ontology-Based Holistic and Probabilistic Framework for Seismic Risk Assessment of Buildings - Minze Xu; Peng Zhang; Chunyi Cui; Jingtong Zhao (Buildings, 2022)
To avoid over-reliance on the identification of building damage states post-earthquake in the seismic risk assessment process, an ontology-based holistic and probabilistic framework is proposed here for seismic risk prediction of buildings with various purposes and different damage states. Based on vulnerability analysis, the seismic risk probabilities of buildings are first obtained by considering the on-site seismic hazard. Taking economic losses and casualties as assessment indicators, a system for seismic risk assessment of buildings, OntoBSRA (Ontology for Building Seismic Risk Assessment), is then developed by combining ontology and semantic web rule language. A case study is carried out to demonstrate the application of the proposed framework and further validate the semantic web rules. The results show that the proposed framework can provide a holistic knowledge base that allows risk assessors or asset managers to predict the consequences of earthquakes effectively, thereby improving efficiency in decision-making.